Distribution of single-walled carbon nanotubes in pyrene containing liquid crystalline asymmetric zinc phthalocyanine matrix - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2014)
A novel pyrene containing asymmetric Zn(II) phthalocyanine (AB3 type) was synthesized and characterized by various spectroscopic techniques as well as elemental analysis. A symmetric polyoxyethylene substituted Zn(II) phthalocyanine (B4 type) derivative was also prepared in order to compare the properties and determine the effect of the pyrene group on the phthalocyanine molecule. Composites of synthesized zinc(II) phthalocyanine-single wall carbon nanotubes (ZnPc-SWCNTs) containing 1 and 2 wt% carbon nanotubes were prepared by mixing these two components in dichloromethane followed by removal of the solvent and drying under vacuum. The liquid crystalline properties of the pure compounds and their composites were investigated in comparison with symmetric polyoxyethylene substituted Zn(II) phthalocyanine (B4 type) by using polarized optical microscopy, differential scanning calorimetry and X-ray diffraction analysis. The distribution of the SWCNTs in the ordered matrix of the columnar mesophase of these derivatives was studied by the method of polarized Raman spectroscopy and scanning electron microscopy (SEM). It was shown that the nature of the mesophases was not altered in these composites. The I(V) dependencies for the films deposited onto interdigitated electrodes were measured and it was shown that the lateral conductivity tends to increase with increasing SWCNT concentration.
Keywords: RAMAN POLARIZATION; ORIENTATION; ALIGNMENT; CHARGE; TRIPHENYLENE; BEHAVIOR; GROWTH